Measuring journalistic peace/war performance: An exploratory study of crisis reporters' attitudes and perceptions. (April 2016) - Neumann, Rico; Fahmy, Shahira
Based on Galtung's concept of peace/war journalism, this exploratory work attempts to advance an empirical method to develop a survey instrument for a reliable and valid assessment of journalists' attitudes toward peace/war performance. The authors propose a measurement index of conflict reporting which combines several practices linked to peace/war journalism. The usefulness of the approach is then demonstrated by quantitative and qualitative evidence from a pilot study based on a survey of worldwide members of The Pulitzer Center on Crisis Reporting . Benefits of the approach and implications for future peace/war survey research are discussed.